2021
DOI: 10.1002/nme.6775
|View full text |Cite
|
Sign up to set email alerts
|

Discrete variable topology optimization for simplified convective heat transfer via sequential approximate integer programming with trust‐region

Abstract: This article presents a discrete variable topology optimization method to solve the simplified convective heat transfer (SCHT) design optimization modeled by Newton's law of cooling. The discrete variable topology optimization is based on the proposed sequential approximate integer programming with trust-region. Due to the discrete variables, identifying the convective boundary, and implementing this design-dependent convective boundary condition can be precisely undertaken. As a result, the consistent precise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 49 publications
(164 reference statements)
0
5
0
Order By: Relevance
“…Liang et al suggested a sequential approximate integer programming with a trust region framework to restrict the range of discrete design variables by linearizing the non-linear trust region constraint [139]. This provided method was also extended into 3D structures and convective heat transfer problems [140,141].…”
Section: Augmented Lagrangementioning
confidence: 99%
“…Liang et al suggested a sequential approximate integer programming with a trust region framework to restrict the range of discrete design variables by linearizing the non-linear trust region constraint [139]. This provided method was also extended into 3D structures and convective heat transfer problems [140,141].…”
Section: Augmented Lagrangementioning
confidence: 99%
“…In addition to the optimization techniques discussed above, a limited number of studies have investigated the Cuckoo Search Algorithm, linear programming, finite volume method (for topology optimization), , and nonlinear least-squares error . However, justification for the applicability and usage of these techniques to different heat transfer problems has been missing in these studies, as not all optimization techniques could fit any problem, , depending on the given constraints and objectives.…”
Section: Introductionmentioning
confidence: 99%
“…However, the level set method has the disadvantage of initialization dependence; thus, the location of convection boundaries will greatly affect the optimization results. More importantly, the above studies did not consider the fact that a structure boundary might be partly convective (Hu et al, 2008;Wang and Qian, 2020;Yan et al, 2021). Hence, it is necessary to identify whether a boundary is convective, adiabatic or partly convective.…”
Section: Introductionmentioning
confidence: 99%